Pregnancy‐related outcomes among women with physical disabilities: A systematic review. Issue 6 (24th August 2021) - Deierlein, Andrea L.; Antoniak, Katherine; Chan, Melany; Sassano, Caprice; Stein, Cheryl R.
Abstract: Background: Disability among women of reproductive age is common; many of these women desire children and do not have impaired fertility. Objectives: To examine the epidemiological literature on perinatal health outcomes among women with physical disabilities. Data sources: We searched Medline and CINAHL for articles published January 2009–April 2020 following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Study selection and data extraction: Eligible studies were observational, quantitative, and reported on physical disabilities in association with prenatal, perinatal, postpartum, and/or infant health outcomes. We included studies that grouped physical and non‐physical disabilities, such as surveys that queried only about general daily life limitations. We excluded case reports, descriptive studies without comparison groups, and studies conducted in low‐ or middle‐income countries. Data extraction was done using predefined data fields. Synthesis: All authors were involved in screening activities, data extraction, and/or quality assessment (rating and areas for bias). Results: A total of 2650 articles were evaluated, of which sixteen met inclusion criteria (8 cross‐sectional studies and 8 retrospective cohort studies). Assessments of disability status and perinatal outcomes widely varied across studies. Studies were rated as poor ( n = 8) or fair quality ( n = 8). Findings suggested that women with physical disabilities were at risk of several adverse outcomes, including caesarean delivery, infections, preterm complications, and maternal post‐delivery hospitalisations, while their infants may be at risk of low birthweight and small‐for‐gestational age. Women classified as having complex/severe disabilities were often observed to be at higher risk of adverse outcomes compared to women with less severe disabilities. Conclusions: Research assessing how physical, functional, and medical restrictions influence health outcomes among women with physical disabilities, from preconception through postpartum, is limited. Longitudinal studies with comprehensive data collection that accurately identify women with physical disabilities are critical to understanding their reproductive health risks and outcomes.